2007
DOI: 10.1002/app.27325
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the interface structure of different surface‐modified nano‐SiO2 on the mechanical properties of nylon 66 composites

Abstract: The nylon 66-based nanocomposites containing two different surface-modified and unmodified SiO 2 nanoparticles were prepared by melt compounding. The interface structure formed in different composite system and their influences on material mechanical properties were investigated. The results indicated that the interfacial interactions differed between composite systems. The strong interfacial adhesion helped to increase tensile strength and elastic modulus of composites; whereas, the presence of modification l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…The interfacial strength between nanosilica and PA6 is a key factor where the surface amino groups of nanosilica can form the chemically bonding action with the end carboxyl groups of PA6, and whether and to what extent the reaction between the surface amino groups of nanosilica and the end carboxyl groups of PA6 occurred usually affect the mechanical strength. The results also indicated that the reacting amino groups was benefi cial to improve the mechanical properties due to the tiny lattice structure via the reaction between surface amino groups and molecular chains of PA6 9, 13 . In addition, the crystal structure inside PA6 is also an important factor for understanding the mechanical properties of PA6/SiO 2 nanocomposites where the α crystal type is benefi cial to the improvement of mechanical strength of nanocomposites 14, 15 , while the diffraction peaks of α crystal gradually increased from PRA0 to PRA5.…”
Section: Crystal Structures Analysismentioning
confidence: 93%
“…The interfacial strength between nanosilica and PA6 is a key factor where the surface amino groups of nanosilica can form the chemically bonding action with the end carboxyl groups of PA6, and whether and to what extent the reaction between the surface amino groups of nanosilica and the end carboxyl groups of PA6 occurred usually affect the mechanical strength. The results also indicated that the reacting amino groups was benefi cial to improve the mechanical properties due to the tiny lattice structure via the reaction between surface amino groups and molecular chains of PA6 9, 13 . In addition, the crystal structure inside PA6 is also an important factor for understanding the mechanical properties of PA6/SiO 2 nanocomposites where the α crystal type is benefi cial to the improvement of mechanical strength of nanocomposites 14, 15 , while the diffraction peaks of α crystal gradually increased from PRA0 to PRA5.…”
Section: Crystal Structures Analysismentioning
confidence: 93%
“…Xu et al [117] observed that silica nanoparticles with a modifi ed surface effectively hindered the diffusion process of polymer chain segments and, at the same time, also acted as a nucleating agent. However, because these two competing processes were acting simultaneously, no distinct changes were observed in the crystallinity of Nylon 66 in the nanocomposites as compared to that of neat Nylon 66.…”
Section: Nylon 66mentioning
confidence: 99%
“…The sol-gel approach, used to synthesize PA6 nanomaterials has received considerable interest in recent decades. However, most previous studies investigated PA6 films or sheets with nanoscale SiO 2 mainly distributed on the surface of the PA6 matrices at low-volume loading [30][31][32][33]. The preparation of PA6/SiO 2 composites, especially microspheres with high dispersion and high loading weight, is more challenging and rarely reported.…”
Section: Introductionmentioning
confidence: 99%